History of the Society of Jesus in North America: colonial and federal - Hughes, Thomas (Longmans, 1907)
Text: v. 1. from the first colonization till 1645.-- v. 2. 1645-1773 -- Documents: v. 1 pt. 1. 1605-1838 -- v. 1 pt. 2. 1605-1838.